Energy security in Pakistan: A quantitative approach to a sustainable energy policy - Sadia Malik; Maha Qasim; Hasan Saeed; Chang Youngho; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2019)
Pakistan imports nearly a third of its energy resources in the form of oil, coal, and liquefied natural gas (LNG). An import-driven energy policy is not sustainable for Pakistan, making it energy insecure in the long term. Besides being a drain on its foreign exchange reserves, it exposes the economy to international energy price shocks, putting the entire economy at risk through inflation. Inflationary pressures reduce the competitiveness of the country's exports, further constraining the economy's capacity to pay for energy imports. This paper analyzes Pakistan's energy security under the 4As framework over the 6-year period of 2011-2017. The 4A methodology attempts to measure and illustrate graphically the change in the energy security of a region by mapping it onto four dimensions: availability, applicability, acceptability, and affordability. The analysis indicates that Pakistan's energy security improved initially over the first 3 years but then deteriorated over the next 3 years. Despite significant investments in the energy infrastructure over the last 5 years, Pakistan continues to be energy insecure. This paper recommends the immediate and rapid adoption of green energy solutions, like distributed solar and smart metering, and increased conservation efforts, like developing and implementing building insulation standards to mitigate energy insecurity.
Keywords: O13; Q4; 330; energy security; Pakistan; renewable energy; 4As framework